Statin treatment increases lipoprotein(a) levels in subjects with low molecular weight apolipoprotein(a) phenotype. (October 2019) - Yahya, Reyhana; Berk, Kirsten; Verhoeven, Adrie; Bos, Sven; van der Zee, Leonie; Touw, Jeanette; Erhart, Gertraud; Kronenberg, Florian; Timman, Reinier; Sijbrands, Eric; Roeters van Lennep, Jeanine; Mulder, Monique
Abstract: Background and aims: We aimed to evaluate the effect of statin treatment initiation on lipoprotein(a) [Lp(a)] levels in patients with dyslipidemia, and the interactions with the apolipoprotein(a) [apo(a)] phenotype, LPA single nucleotide polymorphisms (SNPs) and change in LDL cholesterol. Methods: The study population consisted of patients with dyslipidemia, predominantly familial hypercholesterolemia, who first initiated statin treatment (initiation group; n = 39) or were already on stable statin treatment for at least 4 months (control group; n = 42). Plasma Lp(a) levels were determined with a particle-enhanced immunoturbidimetric assay before and at least 2 months after start of statin treatment in individuals of the initiation group, and at two time points with an interval of at least 2 months in the control group. High and low molecular weight (HMW and LMW, respectively) apo(a) phenotype was determined by immunoblotting, and the common LPA SNPs rs10455872, rs3798220 and rs41272110 by Taqman assay. Results: Plasma Lp(a) levels did not increase significantly in the initiation group (median 20.5 (IQR 10.9–80.7) to 23.3 (10.8–71.8) mg/dL; p = 0.09) nor in the control group (30.9 (IQR 9.2–147.0) to 31.7 (IQR 10.9–164.0) mg/dL; p = 0.61). In patients with the LMW apo(a) phenotype, Lp(a) levels increased significantly from 66.4 (IQR 23.5–148.3) to 97.4 (IQR 24.9–160.4) mg/dL ( p = 0.026) in the initiation group, but not in the control group and not in patients characterized by the HMW apo(a) phenotype. Interactions with common LPA SNPs and change in LDL cholesterol were not significant. Conclusions: Statins affect Lp(a) levels differently in patients with dyslipidemia depending on the apo(a) phenotype. Statins increase Lp(a) levels exclusively in patients with the LMW apo(a) phenotype. Graphical abstract: Image 1 Highlights: High levels of Lp(a) may contribute to the residual cardiovascular risk in statin-treated dyslipidemic patients. Reported data on modulatory effects of statins on plasma Lp(a) levels are inconsistent. Statin treatment increases Lp(a) levels in patients with dyslipidemia, exclusively in those with the LMW apo(a) phenotype. The increase in Lp(a) levels upon statin treatment was not associated with common LPA SNPs or change in LDL cholesterol.